PENGARUH METODE DISKUSI BERBANTUAN MIND MAPPING TERHADAP HASIL BELAJAR MAHASISWA PADA MATA KULIAH SEMANTIK PROGRAM STUDI PENDIDIKAN BAHASA DAN SASTRA INDONESIA UMRAH TAHUN AKADEMIK 2014/2015 - Pujiastuti, Indah (BAHASTRA, 2017)
This research aims to know the influence of the method of discussion-based mind mapping to learning outcomes of Semantics. Discussion and  mind mapping involves the right brain and left, as well as a focus on learning styles of students.  This study is about Praeksperimental Design Static Group Comparison. The population in this study was all student who became grade of 2013 amounthed to 68 people.  The test results are then analyzed by t-test. The result indicated that experimental classes have an average score of 66, while the control class has an average score of 44. T and t count comparison table of experimental groups showed that t count (6.708) > t table (3.21). T and t count comparison table the control group suggests that t count (6.713) > t table (0.678). The results of the Sig (2-tailed) any two groups indicating that the Sig (2-tailed) confidence level < (0.025). Those results indicated was Ho denied and Ha received, which means the discussion using mind mapping the positive effect to the learning outcomes of Semantics.